Find the solution subject to the initial conditions.
dP/dt = -2P P(0)=1
dP/-2P = dt
then do i take the antiderivative? what would i do next??
Calculus - drwls, Thursday, December 4, 2008 at 6:51pm
ln P = -2 t + C
P = e^(-2t + C)
= C' e^-2t where C' is a different arbitrary constant
C' = 1 since P(0) = 1
Therefore P = e^-2t
Calculus - bobpursley, Thursday, December 4, 2008 at 6:53pm
What if P= Ce^at + D
dP/dt= aCe^at and if D is zero..
dP/dt= ac e^at=aP
now if a is -2
P(O)=1=Ce^a0=C so C=1
Now for your question...
Calculus - Daniel, Thursday, December 4, 2008 at 6:59pm